Water Infrastructure finance in Nambia: Analysing the participation of State and non-State actors - Nghipangwa, Simon Tangi (Research of GSB, 2018)
The adverse effects of climate change have had significant impacts on water resources, mostly in dry and semi-arid countries. Therefore, there is a need to provide more water infrastructure. Lack of adequate water infrastructures, most prevalent in the developing countries, negatively affects sufficient supply of clean drinking water and provision of basic sanitation. Infrastructure forms the basic medium for water generation, processing, transportation, and storage. Efforts to improve this in many developing countries have predominantly been the responsibility of the State. However, in recent years, Non-State Actors (NSA) have been increasingly involved in governance and financing of infrastructure projects in developing countries. To explore this further, the research investigated the roles and relationships between State and NSAs in the governance and financing of water infrastructure projects in Namibia. A mixed explorative qualitative and quantitative approach was adopted. It relied on a survey and a case study of State actors and NSAs involved in water infrastructure in Namibia. Data from both the structured infrastructure questionnaires and secondary data from document review (i.e. water-capital project reports) were extracted, classified, and evaluated using statistical analysis tools. Data pertinent to the research were extrapolated to support the analysis of water infrastructure funding and financing structures. This research examined the State of water-infrastructure development finance in Namibia, by analysing the participation of State and non-State actors in water infrastructure development and finance. There is a well-acclaimed global trend towards diminution of State control and management of public infrastructures. Non-State actors now play a more significant role. Importantly, by contrast, this study found a continued dominance of State in water infrastructure development in Namibia; the presence of NSAs in the water infrastructure space is very limited. A Public Private Partnerships Act would allow non-State actors to participate freely in public infrastructure development. The lack of such enabling legislation in Namibia has prevented financial and technical partnerships between the State and NSAs. This absence has kept potential NSAs almost out of the water-infrastructure development business to complement the State. This phenomenon further exacerbates the continued burden on State finance resources to cater for infrastructure development.